PENGARUH DIFFERENTIATION OF SELF TERHADAP EMOTIONAL REGULATION PADA REMAJA DI JABODETABEK - Ying, Chin Li; Aditya, Yonathan (Jurnal Psikohumanika, 2023)
Stress is a phenomenon that is often found among adolescents. This is because the ability to regulate emotions in adolescents is still very minimal. This becomes quite concerning if emotions cannot be regulated properly because it can lead to affecting mental health such as depression to suicide. The purpose of this research is to see how the role of the dimensions of differentiation of self can contribute to the use of the Emotional Regulation strategy. This study involved respondents with the characteristics of teenagers aged 18-25 years and domiciled in Greater Jakarta. Researchers used a sampling technique in the form of purposive sampling. The results of data collection in the field were 128 respondents but after only 108 respondents were declared valid and involved in the final results of the study. The results of data analysis using the JASP program version 0.15.10, with the multiple linear regression test method. The results of the correlation analysis showed that there was only a significant correlation in Cognitive Reappraisal with the Maintaining Identity dimension. On the other hand, the Expressive Suppression strategy is significantly correlated with all dimensions of the Differentiation of Self. This study has fulfilled all the classic assumption tests and regression tests showing that only the Maintaining Identity dimension can contribute significantly positively to the use of Cognitive Reappraisal strategies. On the other hand, the dimensions of Relational Sensitivity and Emotional Distancing can significantly contribute to the use of Expressive Suppression strategies.